2021
DOI: 10.2196/22601
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Smartphone-Based Interventions on Physical Activity in Children and Adolescents: Systematic Review and Meta-analysis

Abstract: Background About 70% of children and adolescents worldwide do not meet the recommended level of physical activity (PA), which is closely associated with physical, psychological, and cognitive well-being. Nowadays, the use of technologies to change PA is of interest due to the need for novel, more effective intervention approaches. The previous meta-analyses have examined smartphone-based interventions and their impact on PA in adults, but evidence in children and adolescents still needs further res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 44 publications
3
87
0
1
Order By: Relevance
“…If the daily step count is decreased by 4000 steps or more, healthcare professionals should directly contact such individuals and check their health status. There are different types of intervention methods to promote physical activity (e.g., in-person, telephone, emails, text messaging, mobile applications, and social media), and among them, the smartphone-based intervention effectively improves total physical activity and daily steps in children and adolescents [39]. In addition, wearable activity trackers are recognized as useful and acceptable healthcare devices in individuals aged >50 years and with chronic disease [40].…”
Section: Future Perspectives Of Wearable Devices During Pandemicsmentioning
confidence: 99%
“…If the daily step count is decreased by 4000 steps or more, healthcare professionals should directly contact such individuals and check their health status. There are different types of intervention methods to promote physical activity (e.g., in-person, telephone, emails, text messaging, mobile applications, and social media), and among them, the smartphone-based intervention effectively improves total physical activity and daily steps in children and adolescents [39]. In addition, wearable activity trackers are recognized as useful and acceptable healthcare devices in individuals aged >50 years and with chronic disease [40].…”
Section: Future Perspectives Of Wearable Devices During Pandemicsmentioning
confidence: 99%
“…Böhm et al [ 28 ] furthermore criticize the quality of mHealth interventions for children and adolescents in this respect and suggest that more age-appropriate solutions are needed. The results of other reviews indicate that smartphone-based mHealth interventions (especially apps) are a versatile strategy for increasing PA and steps in children and adolescents [ 29 ]. For example, Laranjo et al [ 30 ] found an average increase of 1850 steps per day after an mHealth intervention.…”
Section: Introductionmentioning
confidence: 99%
“…A previous systematic review found that smartphone-based interventions were more effective at increasing child PA than adolescent PA [73]. It was suggested that younger participants would have required parental assistance to use the technology, which may have encouraged parental involvement and the monitoring of their child's PA behaviours [73]. One study included in this review found no difference in daily steps, MVPA, or calorie expenditure between adolescents provided with a wearable alone and adolescents and their parent receiving a wearable [66].…”
Section: Effectiveness Of Wearables On Physical Activity Outcomesmentioning
confidence: 98%
“…Thus, caution should be taken when generalising results to all age groups (5 to 19-year-olds). A previous systematic review found that smartphone-based interventions were more effective at increasing child PA than adolescent PA [73]. It was suggested that younger participants would have required parental assistance to use the technology, which may have encouraged parental involvement and the monitoring of their child's PA behaviours [73].…”
Section: Effectiveness Of Wearables On Physical Activity Outcomesmentioning
confidence: 99%